PERUBAHAN BENTUK, FUNGSI DAN MAKNA TENUN SONGKET SIAK PADA MASYARAKAT MELAYU RIAU - Guslinda; Otang Kurniaman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was condected in Kampung Rempak Kabupaten Siak where tenun Siak development area existed during the royal era. Tenun Siak cloth is one of the cultural products of its society that was made and worn by royal family. During the time, Tenun Siak cloth is not only worn by royal family but also by public society other than the royal society with its forms and motives. The objective of the research is to understand of Tenun Siak cloth related to motives, ascesorier and function change and meaning of Tenun Siak cloth pertaining to the user, social status on the society. The research appleied qualitative approach by following method develoved by Milles and Humberman. Data was collected by applying field reseach to the Tenun Siak clocth. Data also being collected from informen, the Siak cloth weaver, traditional expert, headvillagers and the capable men of the village. Informen were determiend by purposive based on necessities. For data validity, it is important to apply checking trustworthiness technic, subtitutive, dependecy and accuracy.The research finds that there has been any change to the Tenun Siak cloth, the product change. Motives and colors are now more varied, as well as form compared to the royal era, it also happens to the use, Tenun Siak cloth is not only for royal family but it is also worn by people in general, in anytime and at any place. Besides, the change also happens to the done tativec conotative meaning and symbol of the Tenun Siak cloth. The change found due to internal change to the weaver by economic motive as well as external change by the use of tool sets and also communication along with technology.